IMPLEMENTASI SERTIFIKASI HALAL TERHADAP MIE GACOAN - Mulyadi Sopiam; Nuniek Dewi Pramanik; Resti Sri Aprilia (JEBS (Journal of Economic and Business Student), 2023)
AbstractWith globalization, free trade and the Asian Economic Community (AEC) causing an increase in the circulation of food and beverage products in Indonesian society. Indonesia is a country with the largest Muslim population in the world. In Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia it is stated that "The state guarantees every resident to embrace their religion according to their beliefs". This article reviews the procedures for obtaining halal certificates for Gacoan noodle products and the implementation of halal certification for Gacoan noodle production. The purpose of writing is to find out the procedure for a halal certificate for gacoan noodle products and to find out the implementation of the application of a halal certificate for gacoan noodle products. The research method used in writing is qualitative research and interviews. The conclusion of this paper is to find out the halal certificate from Mie Gacoan and its implementation on products and the validity period of the halal noodle gacoan certificate, as well as the benefits of halal certificates on traded products to provide protection and legal certainty for the rights of Muslim consumers to products that are not lawful.